2019
DOI: 10.1007/s00204-018-2376-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cyclin-dependent kinases in the adult human retina in relation to CDK inhibitor retinotoxicity

Abstract: Cyclin-dependent kinases (CDKs) are a family of kinases associated predominantly with cell cycle control, making CDK inhibitors interesting candidates for anti-cancer therapeutics. However, retinal toxicity (loss of photoreceptors) has been associated with CDK inhibitors, including the pan-CDK inhibitor AG-012896. The purpose of this research was to use a novel planar sectioning technique to determine CDK expression profiles in the ex vivo human retina with the aim of identifying isoforms responsible for CDK r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…We next focused on the effect of TPD7 treatment on cell cycle progression and the results showed that TPD7 mainly blocked the cell cycle progression at G2/M phase and partially at G1 phase (Figure ). Previously, cyclin‐dependent kinase (CDK) and cyclins function as dynamic regulators of cell cycle progression . CyclinB1 was associated with the G2/M checkpoint control and could form a complex by binding with CDC2, which takes an important part in G2/M phase transition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next focused on the effect of TPD7 treatment on cell cycle progression and the results showed that TPD7 mainly blocked the cell cycle progression at G2/M phase and partially at G1 phase (Figure ). Previously, cyclin‐dependent kinase (CDK) and cyclins function as dynamic regulators of cell cycle progression . CyclinB1 was associated with the G2/M checkpoint control and could form a complex by binding with CDC2, which takes an important part in G2/M phase transition .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, cyclin-dependent kinase (CDK) and cyclins function as dynamic regulators of cell cycle progression. 33 CyclinB1 was associated with the G2/M checkpoint control and could form a complex by binding with CDC2, which takes an important part in G2/M phase transition. 34 And, it was well recognized that CDC2, cyclinD1 and cyclinE are critical molecules in the regulation of cells from G1 phase into S phase.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 21 ] reported that miR-4469 was significantly down-regulated in breast cancer and that miR-4469 suppressed breast cancer metastasis by inhibiting the Wnt/β-catenin pathway. CDK3 is a member of the cyclin-dependent kinase family and is directly involved in cell cycle regulation for G1 exit and S entry [ 22 , 23 ]. The activation of CDK3 leads to G1 arrest and serves an important role in cell proliferation and malignant transformation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some cellular proteins are required for the replication of many viruses, an antiviral inhibiting them should result in no toxic effects to the entire organism. Consequently, no drug targeting these proteins has been developed into an antiviral ( 5 9 ), even though many cellular proteins are targeted by drugs developed for non-infectious diseases, including the cyclin-dependent kinases (CDK) ( 10 , 11 ), which are involved in the replication of many unrelated viruses.…”
Section: Introductionmentioning
confidence: 99%